Troxerutin, a Bioflavonoid, Improves Oxidative Stress in Blood of Streptozotocin-Induced Type-1 Diabetic Rats: Troxerutin improves oxidative stress in diabetic rats - Reza badalzadeh; Leila Chodari; Vajihe ghorbanzadeh (Iranian Journal of Pharmaceutical Sciences, 2017)
Type 1 diabetes is a chronic disease characterized by the body’s inability to produce insulin due to destruction of the beta cells. There is increasing evidence that reactive oxygen species (ROS) play a major role in the development of diabetic complications. The purpose of this study is to investigate the effects of troxerutin administration on oxidative stress markers in blood of STZ-induced diabetic rats. Male Wistar rats were divided into 4 groups as: control (con), control-troxerutin (CON-TRX), diabetes (Dia), diabetic-troxerutin (DIA-TRX). Type 1 diabetes was induced by injection of streptozotocin (STZ) (i.p, 55mg/kg) and lasted for 10 weeks. Animals received oral administration of troxerutin (150 mg/kg) for 4 weeks. At the end of study, malondialdehyde (MDA, the main product of lipid peroxidation), activity of antioxidant enzymes superoxide dismutase (SOD), glutathione peroxidase (GPX), and catalase (CAT) were measured spectrophotometrically. Induction of diabetes with STZ resulted in increased MDA levels and decreased blood antioxidant capacity as compared with those of controls (P<0.05). Pre-treatment of diabetic rats with troxerutin significantly decreased the levels of MDA (P<0.01) and increased the activity of antioxidant enzymes SOD, GPX, and CAT compared to untreated-diabetic groups. Troxerutin had no significant influence on non-diabetic rats. These findings showed that troxerutin may prevent oxidative complications of diabetic circumstances by elevating antioxidant enzymes activities and reducing lipid peroxidation.